Recovery of free amino acids and muscle proteins from codfish (Gadus morhua L.) salting wastewater by sorption on Amberlite XAD16 - Ferraro, Vincenza; Jorge, Ruben Ferreira; Cruz, Isabel B.; Castro, Paula M. L.; Pintado, Manuela E. (Journal of Chemical Technology & Biotechnology, 2014)
BACKGROUND The objective of this research was the valorization of an agro-food industry residue, namely codfish salting wastewater, through the recovery of valuable bioactive compounds. Approximately 200 L of salted wastewater are generated for each ton of fresh codfish, carrying protein and free amino acids at a concentration of c. 10 g L-1, and sodium chloride (NaCl) at c. 250 g L-1. RESULTS Protein and free amino acids were selectively recovered by sorption with the Amberlite XAD16 resin. Food-grade acetone was used to elute amino acids while a solution of sodium hydroxide (NaOH) desorbed protein. Recovery of protein and of hydrophobic to neutral amino acids was 100%; NaCl was also partially recovered from the salting wastewater, at a level of 33%. Kinetics and mechanisms of adsorption and desorption were investigated. CONCLUSIONS The process implemented can be considered as a valuable management option for codfish salting wastewater, it can contribute to the fish industry sustainability and can serve as a source of nutrients. Free amino acids and protein extracts can find application in animal and human nutrition through incorporation into functional food and drinks, as well as in cosmetics and in pharmaceutical formulations.